THE BRAZILIAN POLICY AGENDAS: AN ANALYSIS OF CAPACITY AND DIVERSITY OVER PRIORITIES IN PUBLIC POLICIES FOR THE PERIOD 2003 TO 2014 - Brasil, Felipe Goncalves [UNESP]; Niedhardt Capella, Ana Claudia [UNESP] (Fundacao Getulio Vargas Escola Adm Empresas Sao Paulo, 2019)
This paper aims to present the first results of the research conducted by the Brazilian Policy Agendas Project. The results to be presented and discussed in the paper focus on analyses of the capacity and diversity of presidential attention to public policies in three periods of government: first and second Lula government and Dilma government. The analyses and conclusions corroborate the important theoretical precepts of the agenda-setting studies that evidence maintenance and changes in public policy priorities, that is, incremental moments and moments of change in the agenda. They also point to important movements in the capacity, diversity and elasticity of the governmental agenda, caused, above all, by different moments of institutional and cognitive friction in the domestic and external environments. They show, finally, that variations in the presidency's priorities go far beyond macro systemic changes resulting from partisan and party-ideological changes. Changes in government priorities can and do occur even within the same governments and governments of the same party.
Keywords: Public policies; policy dynamics; government attention; agenda-setting; messages to the Nacional Congress